Habitats and ecological communities of Indiana: presettlement to present - Whitaker, John O; Amlaner, Charles J (Indiana Natural Science, 2012)
In Habitats and Ecological Communities of Indiana, leading experts assess the health and diversity of Indiana's eight wildlife habitats, providing detailed analysis, data-generated maps, color photographs, and complete lists of flora and fauna. This groundbreaking reference details the state's forests, grasslands, wetlands, aquatic systems, barren lands, and subterranean systems, and describes the nature and impact of two man-made habitats-agricultural and developed lands. The book considers extirpated and endangered species alongside invasives and exotics, and evaluates floral and faunal distribution at century intervals to chart ecological change.